The Formation of Anti-Victim Personality in the Context of Sports - Budyakova, T.P. (2020)
In sports pedagogy, there is the problem of the formation of an athlete’s personality, resistant to various factors of victimization. In the framework of the present study, the author applied the case method and interviews with elite athletes along with the method of victimological analysis. Totally, 20 interviews were processed and 40 cases were analyzed by means of qualitative and quantitative content analyses. It was revealed that both victim and anti-victim personalities of elite athletes have almost the same basic substructures (clusters). However, the content of these clusters is different. The personality structures of the athletes that demonstrate the phenomenon of victim personality include such personal affective complexes as the authority complex, the superiority complex and the guilt complex. The structure of anti-victim personality comprises a system of personality attitudes that do not allow athletes to treat themselves as victims, namely to move forward despite obstacles; to regard defeats as valuable experience, etc. It has been proven that unsportsmanlike behavior is a predictor of victim personality among elite athletes. Manifestations of unsportsmanlike behavior testified the athlete’s victim complex that stimulated such incorrect behavior. It was reasoned that high-performance sport is a predictor of the anti-victim personality of the winner only under certain conditions. Anti-victim personality does not allow itself to be perceived as a victim, using psychological attitudes to overcome the difficulties of a sports life, including defeats.